Estudio de prefactibilidad para la instalación de una planta productora de proteína aislada de harina de sacha inchi (Plukenetia volubilis) - Sotomayor Kamiyama, Gabriel Ernesto (2020)
The aim of this study is to determine the technological, economical, financial and social feasibility of the installation of a sacha inchi (Plukenetia volubilis). powder isolated protein production plant. The target market of this project will be Lima Metropolitana, focused on economic sectors A and B. The product will face an estimated demand of 26.764,01 kg in 2018. The sacha inchi (Plukenetia volubilis) isolated protein will be marketed in polyethylene containers and sold online and also distributed to nutrition supplement stores. Having executed an analysis of micro and macro location factors and being “proximity to the market” and “cost of land” the most important ones, the production plant will be located in the district of Lurin. The size of the plant will be 31.439,39 kg. of sacha inchi (Plukenetia volubilis) isolated protein. From a technical point of view, the required technology for the production of sacha inchi (Plukenetia volubilis) isolated protein is acquirable and usable. Finally, having determined the tangible and intangible investments, as well as the necessary working capital, it was estimated that the total investment would be S/. 1.859.337 from which 50% will be financed over a period of 5 years with an effective annual rate of 15%. The economic evaluation results in a net present value of S/. 44.279 with an internal rate of return of 18,84%, 1,02 of benefit/cost ratio and 4,93 years of recovery period. The financial evaluation determines a net present value of S/. 239.887, an internal rate of return of 25,74, 1,26 B/C ratio and a recovery period of 4,55 years.